2022
DOI: 10.3389/fonc.2022.927088
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Location May Independently Predict Survival in Patients With M0 Squamous Cell Carcinoma of the Penis

Abstract: BackgroundTo determine the association between tumor location and both clinicopathological characteristics and the survival of patients with M0 squamous cell carcinoma of the penis (SCCP).MethodsData of 455 patients diagnosed with M0 SCCP between 1975 and 2018 were collected from the Surveillance, Epidemiology, and End Results (SEER) database of the United States National Cancer Institute. The effects of tumor location on overall survival (OS) and penile carcinoma-specific survival (PCSS) were analyzed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Furthermore, tumor size was proven to be a key predictor in our DM-predicting nomogram. In contrast, tumor location, though considered as a risk factor, showed minimal impact on prognosis or metastasis rate in PC ( 24 , 25 ). Our study acknowledges certain limitations, including the lack of external validation and incomplete data on metastatic sites and metastatic patterns.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, tumor size was proven to be a key predictor in our DM-predicting nomogram. In contrast, tumor location, though considered as a risk factor, showed minimal impact on prognosis or metastasis rate in PC ( 24 , 25 ). Our study acknowledges certain limitations, including the lack of external validation and incomplete data on metastatic sites and metastatic patterns.…”
Section: Discussionmentioning
confidence: 95%
“…Previous cohort studies established that patient age, pathological stage and tumour grade correlate independently with lymph node involvement [19]. Further work has identified that adding tumour size and location variables could generate an LNM prediction nomogram with a calibration slope of 0.9 and a c-index of 0.776 [6,20]. A meta-analysis of 4800 pSCC patients identified additional markers of LNM [5].…”
Section: Predictive Nomogrammentioning
confidence: 99%